2010
DOI: 10.1086/651083
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Early Oseltamivir Therapy on Viral Shedding in 2009 Pandemic Influenza A (H1N1) Virus Infection

Abstract: Prolonged viral shedding was noted in young immunocompetent adults with mild pandemic influenza (H1N1) 2009 despite receipt of oseltamivir. When prescribed during the first 3 days of illness, oseltamivir shortened the duration of viral shedding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
118
3
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 16 publications
13
118
3
2
Order By: Relevance
“…These results agree with those of previous studies 13, 18. A recent Italian study19 has reported that the duration of viral shedding is significantly reduced when therapy is initiated within 2 days of symptom onset.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results agree with those of previous studies 13, 18. A recent Italian study19 has reported that the duration of viral shedding is significantly reduced when therapy is initiated within 2 days of symptom onset.…”
Section: Discussionsupporting
confidence: 93%
“…With regard to 2009 H1N1 influenza, Ling et al 18. have reported that younger immunocompetent adults show prolonged shedding, while Cao et al 13.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, delayed oseltamivir therapy was significantly found in patients with lung involvement. In consistent with previous reports, 35 , 40 , 41 our data recommended an early treatment with oseltamivir for patients whenever 2009 pandemic influenza A (H1N1) is diagnosed or epidemiologically suspected, regardless of age, and this may be particularly important for those with pulmonary involvement.…”
Section: Discussionsupporting
confidence: 91%
“…Studies have shown that prolonged clearance of nasopharyngeal influenza viral RNA load is associated with the severity of the disease, and a rapid decrease in viral load was noted as of the first day of oseltamivir initiation (6,14). It was reported in the study conducted by Jain et al (15) that antiviral treatment was not initiated in any one of the patients who died of influenza in the first 48 h after the onset of symptoms.…”
Section: Discussionmentioning
confidence: 99%